Sistem Informasi Manajemen Berbasis Komputer Untuk Meningkatkan Efisiensi Penyelengaraan Makanan Pada Instalasi Gizi Rumah Sakit Umum Daerah Prof.Dr.H.M.Anwar Makkatutu Bantaeng - Nur Rahmi; Prof.Amir Imbaruddin,MDA,Ph.D.; Dr.Najmi Kamariah,SE,M.Si. (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
One of the main activities of hospital nutrition services is the provision of meals for patients in the hospital. The goal is to provide quality food in accordance with the nutritional needs, cost, safety and acceptance of the patient to achieve optimal nutritional status The food management information system currently used in the Nutrition Installation of Rsud Prof. DR H M Anwar Makkatutu Bantaeng is still using a manual (conventional) system, starting from calculating the need for foodstuffs to ordering foodstuffs. This is due to the unavailability of applications that can more efficiently save energy and time. So far, calculating food needs requires a long time and energy is needed by more than one person. The type of research method used in this research is a quantitative quasi-experimental research method which aims to show a causal relationship and to investigate the relationship and clarify the causes of events, where in this study it focuses on the use of energy and the duration of time used before and after using the application. computers for food management activities in the Nutrition Installation, in this case the calculation of food needs. Based on the results of the research, before and after using a computer-based management information system application to improve the efficiency of food administration at the Rsud nutrition installation, Prof. DR. HM Anwar Makkatutu Bantaeng (SPMIG), there was a difference in time duration, where the time used in calculating the need for foodstuffs was shorter or shorter. Food administration at the Nutrition Installation of Prof. DR H Makkatutu Bantaeng Hospital before using the SPMIG application software an average of 180 minutes - 210 minutes and after using the SPMIG application software the average was 1 - 10 minutes, so the time difference used was 170 minutes.